LOCAL INITIATIVES FOR THE UNEMPLOYMENT COUNTERACTION IN THE MAZOVIA PROVINCE - Marzena Kacprzak (Polityki Europejskie, Finanse i Marketing)
In the dynamically developing market economy there is a variability in the intensity of the processes associated with the occurrence of imbalances in the labor market, which leads to unemployment. Unemployment shows the inefficiency of the labour supply and labour demand adjustment. Sizes and multiple consequences of unemployment justify its recognition as a kind of twenty-first century plague. 1 Mazovia Province is both one of the most actively developing regions and one of the largest regional labor markets in Poland. However, the region is characterized by a high degree of diversity in terms of development. On the one hand, there is highly developed capital city Warsaw and on the other - peripheral areas with worse parameters. This is why it should be aimed to perform the activities supporting local initiatives to avoid unemployment. The main thesis of this paper is to show that the local initiatives aimed at counterpartying unemployment and entrepreneurship promotion, are modern instruments used to monitor and predict changes in the labor market, skills of employees, creation of new jobs, gain work experience.